Pedagogical Competence Towards Technology-driven Instruction on Basic Education - Mariscal, Liza L.; Albarracin, Melanie R.; Mobo, Froilan D.; Cutillas, Anesito L. (Future Science / FSH-PH Publications, 2023)
This study investigates the pedagogical competence of elementary school teachers in integrating educational technology in the classroom. Pedagogical competence involves creating effective learning environments, designing activities that cater to different learning styles, and using appropriate teaching strategies. Technology integration in education has opened up new opportunities for interactive learning experiences. The study found that elementary school teachers had a positive attitude towards educational technology, and most reported having high levels of competence in its use. However, the level of pedagogical competence toward educational technology varied significantly among teachers. Hence, the study emphasizes the need for programs and interventions to improve teachers’ pedagogical competence in integrating educational technology into their teaching practices. Teachers must identify appropriate technological tools and resources to effectively incorporate educational technology to support their teaching objectives and engage students in meaningful learning experiences. Teachers must also assess students’ technical skills and design activities appropriate for their technological competency level. The study recommends that elementary school teachers undergo training to improve their pedagogical competence in using educational technology. Thus, integrating technology into education is crucial in providing high-quality education in the 21st century. Programs are needed to improve teachers’ pedagogical competence in incorporating it into their teaching practices.